Profiling the research landscape on cognitive aging: a bibliometric analysis and network visualization - Othman, Zahiruddin; Abdul Halim, Ahmad Shahril; Azman, Khairunnuur Fairuz; Ahmad, Asma Hayati; Zakaria, Rahimah; Mohamed Salam, Sirajudeen Kuttulebbai Naina; Wijaya, Adi; Safinaz, Tunku Puteri Intan (Frontiers Media S.A., 2022)
Objectives: This study aimed to profile the cognitive aging research landscape from 1956 to 2021.